Willingness toward voluntary counseling and testing and associated factors among tuberculosis infected patients at public hospitals in Addis Ababa, Ethiopia - Sifer, Samuel Dessu; Getachew, Milkiyas Solomon (Frontiers in Public Health, 2024)
Background: Voluntary counseling and testing for HIV has proven to be a highly effective and cost-efficient approach in many locations, yielding excellent results. It serves as a gateway to a range of HIV-related services, including the provision of antiretroviral drugs. Therefore, this study was aimed to assess the willingness towards VCT and associated factors among TB infected patients at Public Hospitals in Addis Ababa, Ethiopia; 2023.Ababa from 1 st to 30 th of March 2023 with 235 participants using systematic random sampling.Trained data collectors employed a pretested data extraction tool for information gathering.Vriables with P-value less than 0.05 in the multivariable logistic regression were considered statistically significant.The prevalence of willingness towards VCT among TB infected patients was (78.3%, 95%CI: 72.8, 83.4). Individuals with a primary education level (AOR: 6.32; 95%CI: 1.65, 24.25), government employees (AOR: 5.85; 95%CI: 1.78, 19.22) and private employees (AOR: 3.35; 95%CI: 1.12, 10.01), good knowledge of VCT (AOR: 3.12; 95%CI: 1.36, 7.16), perceived a higher risk (AOR: 6.58; 95%CI: 2.44, 17.73) and perceived stigma (AOR: 14.95; 95%CI: 4.98, 44.91) were factors associated with willingness towards VCT.Voluntary Counseling and Testing in this study was higher than in previous studies, it falls below the UNAIDS target of 90% of people knowing their HIV status. Notably, factors such as level of education, occupation, knowledge, perceived risk, and perceived stigma emerged as independent factors significantly associated with the willingness of TB-infected patients to undergo VCT. These findings underscore the importance of considering socio-demographic characteristics, knowledge levels, and psychosocial factors in designing strategies to enhance VCT acceptance among TB-infected individuals.